2019
DOI: 10.1177/1046496419874498
|View full text |Cite
|
Sign up to set email alerts
|

Language Matters: The Double-Edged Role of Linguistic Style Matching in Work Groups

Abstract: Linguistic style matching (LSM) refers to a similar linguistic style among conversation partners. We examine the effects of LSM on perceived team performance and perceived social support in real work groups. We propose that team tenure moderates the relationship between LSM and perceived performance such that LSM and performance are positively related for teams with low tenure and negatively related for teams with high levels of tenure. We also propose that LSM and perceived social support are positively relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 58 publications
(93 reference statements)
0
32
0
Order By: Relevance
“…Our results fundamentally tell us two things about LS: Having a conversation partner increases our use and structure of function words, leading to a more uniform use of LS. Building on research on language style matching—the process of adapting one’s language style to someone else over the course of a conversation (Müller‐Frommeyer et al, 2019)—these changes might be indicative of an increasing similarity in LS of the conversation partners (e.g., Heuer et al, 2019; Ireland et al, 2011; Niederhoffer & Pennebaker, 2002). Additionally, these results could be reflective of the social nature of LS—two people interacting with each other create their own shared worldview.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results fundamentally tell us two things about LS: Having a conversation partner increases our use and structure of function words, leading to a more uniform use of LS. Building on research on language style matching—the process of adapting one’s language style to someone else over the course of a conversation (Müller‐Frommeyer et al, 2019)—these changes might be indicative of an increasing similarity in LS of the conversation partners (e.g., Heuer et al, 2019; Ireland et al, 2011; Niederhoffer & Pennebaker, 2002). Additionally, these results could be reflective of the social nature of LS—two people interacting with each other create their own shared worldview.…”
Section: Discussionmentioning
confidence: 99%
“…This is a deviation from previous research on specific components of LS, which analyzed all function word categories individually (e.g., Mehl & Pennebaker, 2003). Based on the definition of LS as one construct represented by overall function word use (Chung & Pennebaker, 2007) and the operationalization of LS in existing studies on language style matching (e.g., Gonzales et al, 2010; Heuer et al, 2019), we chose this approach as we are interested in the changes in overall LS use. However, we acknowledge that previous research found significant differences in the use and function of individual function word categories (e.g., Pennebaker, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In doing so, people engaged in a conversation (speakers) may exhibit similar lexical (i.e., word choice) and syntactic (i.e., sentence structure) properties in their utterances, presumably because greater lexical and syntactic alignment improves efficiency in communication (Semin 2007). In fact, many scholars have examined linguistic similarity among speakers, revealing positive associations with cohesion (Dong 2005;Heuer et al 2020), trust (Scissors et al 2009), and task performance (Dong et al 2004;Foltz et al 2003;Fusaroli et al 2012;Gorman et al 2003;Richardson et al 2019;Yilmaz 2016). Here, we outline approaches which have yielded some promising results in human-human teams, including their computation, relevant findings in the literature, and how they may be adapted and improved for understanding cohesion, trust, and performance in human-autonomy teams.…”
Section: Linguistic Synchronymentioning
confidence: 99%